Do assisted reproductive technologies and in vitro embryo culture influence the epigenetic control of imprinted genes and transposable elements in children?. Issue 2 (15th December 2020) - Barberet, J; Binquet, C; Guilleman, M; Doukani, A; Choux, C; Bruno, C; Bourredjem, A; Chapusot, C; Bourc'his, D; Duffourd, Y; Fauque, P
Abstract: STUDY QUESTION: Do assisted reproductive technologies (ART) and in vitro embryo culture influence the epigenetic control of imprinted genes (IGs) and transposable elements (TEs) in children? SUMMARY ANSWER: Significant differences in the DNA methylation of IGs or transposon families were reported between ART and naturally conceived children, but there was no difference between culture media. WHAT IS KNOWN ALREADY: There is concern that ART may play a role in increasing the incidence of adverse health outcomes in children, probably through epigenetic mechanisms. It is crucial to assess epigenetic control, especially following non-optimal in vitro culture conditions and to compare epigenetic analyses from ART-conceived and naturally conceived children. STUDY DESIGN, SIZE, DURATION: This follow-up study was based on an earlier randomized study comparing in vitro fertilization outcomes following the use of two distinct culture media. We compared the epigenetic profiles of children from the initial randomized study according to the mode of conception [i.e. ART singletons compared with those of a cohort of naturally conceived singleton children (CTL)], the type of embryo culture medium used [global medium (LifeGlobal) and single step medium (Irvine Scientific)] and the mode of in vitro fertilization (i.e. IVF versus ICSI). PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 57 buccal smears were collected from 7- to 8-year-old children. The DNA methylation profiles of four differentially methylated regions (DMRs) of IGs ( H19/IGF2 : IG-DMR, KCNQ1OT1 : TSS-DMR, SNURF : TSS-DMR, and PEG3 : TSS-DMR) and two TEs (AluYa5 and LINE-1) were first assessed by pyrosequencing. We further explored IGs and TEs' methylation changes through methylation array (Human MethylationEPIC BeadChip referred as EPIC array, Illumina). MAIN RESULTS AND THE ROLE OF CHANCE: Changes in the IGs' DNA methylation levels were found in ART children compared to controls. DNA methylation levels of H19/IGF2 DMR were significantly lower in ART children than in CTL children [52% versus 58%, P = 0.003, false discovery rate (FDR) P = 0.018] while a significantly higher methylation rate was observed for the PEG3 DMR (51% versus 48%, P = 0.007, FDR P = 0.021). However, no differences were found between the culture media. After observing these targeted modifications, analyses were performed at wider scale. Again, no differences were detected according to the culture media, but imprinted-related DMRs overlapping promoter region near the genes major for the development ( MEG3, BLCAP, and DLX5 ) were detected between the ART and CTL children. LIMITATIONS, REASONS FOR CAUTION: The sample size could seem relatively small, but the high consistency of our results was ensured by the homogeneity of the cohort from the initial randomized study, the standardized laboratory techniques and the robust statistical analyses accounting for multiple testing. WIDER IMPLICATIONS OF THE FINDINGS: Although this study did not report DNA methylation differences depending on the culture medium, it sheds light on epigenetic changes that could be observed in some children conceived by ART as compared to CTL children. The clinical relevance of such differences remains largely unknown, and it is still unclear whether such changes are due to some specific ART procedures and/or to parental infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by funding from the Agence Nationale pour la Recherche ('CARE'-ANR JCJC 2017). The authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: Not concerned.